Influence of institutional policy factors on learners' academic achievement in two distance learning institutions in Nigeria (2019)
This study examined the influence of institutional policy factors (learners' support services, course material development, information communication technology', staff capacity development, quality assurance and feed back method) on learners' academic achievement in two distance learning institutions in the Southwestern Nigeria. The study was anchored on Kember's system model, while the descriptive survey design was adopted. The National Open University of Nigeria (NOUN) and Distance Learning Centre (DLC), University of Ibadan that are foremost distance learning institutions are purposively selected. The proportional to size sampling technique was adopted in selecting 10.0% of learners across 200 to 500 cohorts in the two institutions: NOUN -1,120 and DLC - 636. Learner Support Services (r-0.86). Course Material Development (r=0.84), Information Communication Technology(r=0.83), Staff Capacity Development( r=0.80), Quality Assurance(r=0.78), Feedback Method(r=0.75) questionnaires and students' cumulative grade performance were used for data collection. Data were analysed using descriptive statistics and Pearson Product Moment Correlation Coefficient at 0.05 level of significance. Learners' support services (r=0.67), course materials (r=0.63), information communication technology (r=0.65). staff capacity development (r=0.39). quality assurance (r=0.31) and feedback method (r=0.35) had positive significant correlations with learners' academic achievement. Learners' support services, course material development, information communication technology, staff capacity development, quality assurance and feedback method policies contributed to learners' academic achievement in distance learning institutions in the Southwestern Nigeria. The management and staff of distance teaming institutions should ensure effective implementation of these policies in order to assist and improve learners' academic achievement.